Entrepreneurship and Sustainable Development Goals: A Multigroup Analysis of the Moderating Effects of Entrepreneurship Education on Entrepreneurial Intention - Ashari, H. (MDPI, 2022)
The role of entrepreneurs in attaining Sustainable Development Goals (SDGs) is para-mount. Entrepreneurs with strong awareness and commitment to sustainable development help to attain almost all SDGs, as they create businesses that will help employment, eliminate poverty, provide decent work and economic growth, help to reduce hunger, assist in attaining good health and wellbeing, help to achieve affordable and clean energy, and enhance their industries. Realizing the importance of entrepreneurs and entrepreneurship, the government of Malaysia has taken proactive actions to develop and inculcate the entrepreneurial mindset through entrepreneurship education at higher education. This study aims to apply the Theory of Planned Behavior (TPB) to analyze the effect of an entrepreneurship course on entrepreneurial intentions of the engineering students at Universiti Teknologi Petronas, as entrepreneurial intention is effective in predicting behavior. A quantitative technique and descriptive crossâsectional study have been employed to collect data. The result of this study indicates that the TPB explains and predicts the entrepreneurial intention. However, the Multigroup Analysis (MGA) results show that attending the entrepreneurship course does not increase the strength of the relationship between the exogenous and endogenous construct compared to those who do not attend the course. The results of this study raise a positive implica-tion toward the improvement of the course curriculum and the teaching pedagogy. An inâdepth qualitative study to understand the issue will help to improve the curriculum and pedagogy of entrepreneurship education, and eventually enable a realization of the governmentâs aspirations. Â© 2021 by the authors. Li-censee MDPI, Basel, Switzerland.